Penerapan On The Job Training Terhadap Keterampilan Kerja Pegawai Frontliner PT.Transrekreasindo Surabaya - Atiqoh, Ayu Zumatul; Mustaji, Mustaji; Mariono, Andi (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This study aims to determine the effect of implementing on the job training on the performance skills of frontliner employees. The type of research used is experimental with a quantitative approach and the research design is quasi-experimental. The population in this study was 60 employees from 3 different branches. The purpose of data analysis is to determine the magnitude of the relationship and the effect of the independent variable (X) on the dependent variable (Y). The results obtained by linear regression test which shows that the effect of on the job training on job skills is 73.9%, of which the rest is influenced by other factors. The t-count value of 6.060 with a sig value of 0.000 <0.05 can be interpreted that there is a significant influence between on the job training on employee work skills. So that it proves that all that can be drawn from the results of the analysis is that there is a significant influence between the application of on the job training to the work skills of frontliner employees of PT. Transrekreasindo Surabaya.